EFFICASY OF A NEW PREPARATION FOR TUBERCULOSIS DIAGNOSTICS IN CHILDREN AND ADOLESCENTS - L. A. Barishnikova; N. O. Lebedeva; L. I. Katkova; S. А. Vdovenko; E. V. Ilyasova; A. M. Kryukova; O. I. Sidorenko (Вопросы современной педиатрии)
The efficacy of recombinant TB allergen in tuberculosis diagnostics in children and adolescents was estimated by the single-step full expansion method. The results were compared with the ones of routine Mantoux method. Seventy eight children admitted to the somatic clinics and 1377 healthy children from preschool and school educational institutions were examined. The reactions to recombinant TB allergen were registered less frequently, than to Mantoux test: 2,5 times less frequently among the hospital patients and 11 times less frequently among the healthy children. Tuberculosis was revealed in 3,8% of hospital patients and in 0,3% of all the examined patients with the new preparation. It is necessary to introduce the tuberculosis screening with recombinant TB allergen among the adolescent population.